Does Emigration Hurt the Economy? Evidence from Lithuania - Kasnauskiene, Gindrute; Kavalnis, Remigijus (Organizations and Markets in Emerging Economies, 2021)
This study explores the economic impact of population emigration with special reference to the case of Lithuania. For this reason, we developed a SVAR model and applied related IRF and FEVD tools using quarterly data for the period of 2001-2020. Our findings reveal that a positive shock in emigration is related to lower unemployment. It is also found that the increased emigration is linked to higher real wage growth but with a lower confidence interval. Moreover, our estimates suggest that international out-migration increases real GDP growth in the short term, with no significant effects in the long run perspective. Finally, we found that most of the emigrants-to-be were inactive for a long term prior to departure, which offers a new look into the consequences of Lithuanian emigration, suggesting that the economic losses of emigration could be overstated. This study contributes to the knowledge about the impact of emigration on the economy and specifies directions for further studies in the field.